Community Empowerment Through Training on Coffee Waste Briquette Production as an Environmentally Friendly Alternative Energy Source - Machmud Al Amrie; Adi Aspian Nur; Risnafaty Risnafaty (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The increase in global coffee consumption has an impact on the accumulation of coffee grounds waste which has not been utilized optimally, even though it has potential as a biomass-based alternative energy source. This condition also occurs in Lebong Village, Tanjung Palas Hilir District, where coffee waste continues to increase along with the development of household-scale coffee shop businesses, while community capacity in managing waste and utilizing alternative energy is still limited. This research aims to increase people's knowledge and skills in processing coffee grounds waste into economically valuable briquettes. The method used is a participatory approach through technical training, counseling and production assistance that involves the community directly. The research results show an increase in understanding, technical skills and environmental awareness in the community in utilizing waste into alternative energy products. Apart from that, this activity also opens up new business opportunities based on local potential which contributes to improving the community's economy. The implications of this research confirm that the use of coffee waste as briquettes not only supports sustainable environmental management, but also strengthens energy independence and community economic empowerment based on local resources.Peningkatan konsumsi kopi global berdampak pada akumulasi limbah ampas kopi yang belum dimanfaatkan secara optimal, padahal memiliki potensi sebagai sumber energi alternatif berbasis biomassa. Kondisi ini juga terjadi di Desa Lebong, Kecamatan Tanjung Palas Hilir, di mana limbah kopi terus meningkat seiring berkembangnya usaha kedai kopi skala rumah tangga, sementara kapasitas masyarakat dalam pengelolaan limbah dan pemanfaatan energi alternatif masih terbatas. Penelitian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan masyarakat dalam mengolah limbah ampas kopi menjadi briket bernilai ekonomis. Metode yang digunakan adalah pendekatan partisipatif melalui pelatihan teknis, penyuluhan, serta pendampingan produksi yang melibatkan masyarakat secara langsung. Hasil penelitian menunjukkan adanya peningkatan pemahaman, keterampilan teknis, serta kesadaran lingkungan masyarakat dalam memanfaatkan limbah menjadi produk energi alternatif. Selain itu, kegiatan ini juga membuka peluang usaha baru berbasis potensi lokal yang berkontribusi terhadap peningkatan ekonomi masyarakat. Implikasi penelitian ini menegaskan bahwa pemanfaatan limbah kopi sebagai briket tidak hanya mendukung pengelolaan lingkungan yang berkelanjutan, tetapi juga memperkuat kemandirian energi dan pemberdayaan ekonomi masyarakat berbasis sumber daya lokal.